(untitled) (City: History, Culture, Society, 2021)
The article considers the process of using ancient Rus building materials in burial structures of the Modern Age in the necropolis of the Church of the Savior in Brestove. The main periods of researches of the Spas necropolis from 1862 to 2019 are analyzed. According to scientific reports, we are selected data on burials of the XII-XIX centuries, which contained ancient Rus building materials: plinth and slabs of pyrophyllite shale. The main attention is focused on the information obtained during the research and rescue research in 2018-2019, where we are recorded nine burials (XVII-XIX centuries) with partial or complete fencing with ancient Russ building materials. Today, building materials of the Old Rus period on the territory of the Spas necropolis are found in the form of part of the burial structure, additional elements in the arrangement of the tomb and in the filling of burial structures. Collected and processed set of materials provides additional data for the reconstruction of historical events associated with the decline and reconstruction of the church. The fixation of such burial structures, in turn, also provides indirect data on the traditions of the funeral rite of the inhabitants of Pechersk town and the military of the Kyiv fortress in the XVII-XIX centuries. - parishioners of the Church of the Savior in Berestove.